Clinical aspects of Emery-Dreifuss muscular dystrophy. (1st January 2018) - Madej-Pilarczyk, Agnieszka
ABSTRACT: Emery-Dreifuss muscular dystrophy (EDMD), clinically characterized by scapulo-humero-peroneal muscle atrophy and weakness, multi-joint contractures with spine rigidity and cardiomyopathy with conduction defects, is associated with structural/functional defect of genes that encode the proteins of nuclear envelope, including lamin A and several lamin-interacting proteins. This paper presents clinical aspects of EDMD in context to causative genes, genotype-phenotype correlation and its emplacement within phenotypic spectrum of skeletal muscle diseases associated with envelopathies.